Inside/Outside. Sceneries of an inhabiting to-come - Rispoli, Micol; Rispoli, Francesco (Itinerari, 2024)
There are various ways of approaching the design of inhabiting. Many have to do with one idea of architecture abstracted from the specific conditions in which it is set, and another that instead uses precisely these conditions, les moyens du bord, as the tools of construction, as does the bricoleur. This applies to dwellings, cities and what we still call territories. The climate crisis requires us, now more than ever, to follow Isabelle Stengers’ (2018; tr. it. 2021, p. 61) indication: to engage with and for the world in which we live.